PERAN INTERAKSI SOSIAL DALAM KESEJAHTERAAN MENTAL GEN Z: ANALISIS PENTINGNYA MEMILIKI ‘SOMEONE TO TALK’ - Aisyah Nur Fadhilah; Mirna Nur Alia Abdullah; Muhammad Retsa Rizaldi Mujayapura (Yayasan Literasi Sains Indonesia, 2025)
Mental health has now become an important concern around the world, especially among Generation Z. Gen Z was born in the midst of rapid technological development with all activities and interactions that are all online and virtual, providing a lot of social pressure that arises so that it affects the mental well-being of Gen Z. Social interaction has an important role in this problem, the existence of social support through ‘Someone To Talk’ such as family, friends, partners or even professionals can help prevent or reduce mental disorders that a person feels. Through a literature review, this article will analyze the mental health issues of Gen Z and how ‘Someone To Talk’ plays a major role in preventing and managing mental illness in Gen Z. Through this discussion, this article hopes to provide a deeper insight into the role of social interaction through ‘Someone To Talk’ in maintaining Gen Z's mental well-being. The findings from this study show how important social support is in reducing the levels of anxiety, depression and stress that Gen Z often experiences.